Penerapan Rendam Kaki Air Hangat Terhadap Resiko Perfusi Serebral Tidak Efektif Pada Pasien Dengan Indikasi Preeklamsia Berat - Dyah Nurita Hany; Anis Ardiyanti; Rinda Intan Sari (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Severe preeclampsia is a condition characterized by systolic blood pressure exceeding 160 mmHg and diastolic pressure exceeding 110 mmHg, occurring after 20 weeks of gestation and accompanied by edema and proteinuria. One intervention used to save both mother and fetus is a cesarean section. This final nursing scientific paper analyzes the implementation of evidence-based practice, specifically warm foot soak therapy, for mothers with severe preeclampsia during the pre- and postpartum periods who are at risk for ineffective cerebral perfusion. This descriptive case study method used a nursing care approach. Assessment results identified five major nursing problems, including the risk for ineffective cerebral perfusion. After four days of warm foot soak therapy, this problem was resolved, as blood pressure decreased from 147/101 mmHg to 120/88 mmHg. Conclusion: Warm foot soak therapy effectively lowers blood pressure in pre- and postpartum mothers with severe preeclampsia. Recommendation: Nurses can implement warm